The role of corporate governance and dividend policy as an alignment mechanisms to CEO compensation and firm's performance - Farzan, Yahya (2017)
Public perception of CEO compensation is evidently unfair as inefficient compensation structures that violate the rights of shareholders result in principal-agent problems. In order to mitigate this issue, theorists argued that executive compensation should be aligned with firm performance. Owing to the prevalence of agency conflicts in Pakistan, this study investigated the effect of firm performance and characteristics on CEO compensation in the capital market of Pakistan. Furthermore, consistent with prior theoretical arguments, this study examined the role of dividend policy and corporate governance as moderators to ensure their effect on pay-performance link. After data cleaning, this study utilized 284 Pakistani- listed companies (PSX) over the period 2010 to 2014. The findings from Multiple Linear regression showed that CEO compensation is positively aligned to operating performance, market performance, firm size and market share, however, no empirical evidence was found regarding the effect of growth opportunities on CEO compensation. The findings also indicated that family owners align their CEO‘s compensation with operating performance, institutional owners with market performance and firm size, and foreign investors with market share. Thus, these ownership structures play vital roles in mitigating agency conflicts in an organization. It was also revealed that optimal board size could strengthen the pay-performance link. On the other hand, CEO duality and dividend policy could distort the pay-performance link. Contrary to theoretical arguments, dividend policy cannot act as a substitute control device in the absence of strong corporate governance. The role of independent directors as an alignment mechanism to operating performance and CEO compensation is evident but due to their lower level of representation on the board, they have no influence over other accounting and market- based performance metrics. The study provides various theoretical and practical implications to improve corporate governance and compensation practices especially in the perspective of Pakistan.